نقد متن الحديث عند الصحابة: السيدة عائشة رضيالله عنها نموذجا = Textual criticism among the companions: the example of A'isha - Fettane, Amar (2014)
The content of this poster article sheds light on an important aspect of the sciences of Hadith, that is, textual criticism . It has dealt with this topic by showing the historical roots of Hadith textual criticism and its origination with the Companions since the early decades of Islam. It has also demonstrated the critical attitude that characterized the bearers and narrators of Hadith from the time of the Prophet until later times. To illustrate this trend, a number of Hadith instances showing the Companions’ emending and correcting one another’s narrations, especially A’isha may God Almighty be pleased with her, have been studied. Special attention has been paid to uncover and elucidate the methods used in the textual criticism of Hadith, to highlight the points of criticism and to assess the scholars’ views in this respect. The study has combined analytical and critical methods to treat the different aspects of the subject.